Hydrothermal methane fluxes from the soil at Lakki plain (Nisyros Island, Greece) - D’Alessandro, W.; Gagliano, A. L.; Kyriakopoulos, K.; Parello, F. (Bulletin of the Geological Society of Greece, 2013)
Methane and CO2 flux measurements from the soils were made with the accumulation chamber method in Lakki plain covering an area of about 0.06 km2 including the main fumarolic areas of Kaminakia, Stefanos and Phlegeton. Flux values measured at 77 sites range from –3.4 to 1420 mg m-2 d-1 for CH4 and from 0.1 to 383 g m-2 d-1 for CO2. The three fumarolic areas show very different methane degassing patterns, Kaminakia showing the highest flux values. Methane output can be estimated in about 0.01 t a-1 from an area of about 2500 m2 at Phlegeton, about 0.1 t a-1 from an area of about 20,000 m2 at Stefanos and about 0.25 t a-1 from an area of about 30,000 m2 at Kaminakia. The total output from the entire geothermal system of Nisyros should not exceed 1 t a-1. Previous estimates of the CH4 output at Nisyros, based on soil CO2 output and CH4/CO2 ratios in fumarolic gases, were more than one order of magnitude higher. The present work further underscores the utmost importance of direct CH4 flux data.